The Complex Role of Microbial Parasites in Human Health: Their Benefits, Risks, And Impact on the Body And Genes: Areview - Al-Hilfi, Athraa A. A.; Al-Alak, Sanna J. T.; Abu-Mejdad, Najwa M. J. A. (American Journal of Biology and Natural Sciences, 2024)
Microbial parasites play a complex role in human health, with effects ranging from beneficial to harmful. Some cause severe diseases, while others support the immune system or help maintain microbiome balance. These parasites can influence gene expression, contributing to varied immune responses. The Demodex mite is a notable example, naturally residing in hair follicles and sebaceous glands, aiding in the removal of oils and dead skin cells. However, excessive proliferation can lead to skin issues, such as blepharitis or associations with rosacea. The interaction between this parasite and the immune system may result in genetic changes in immune expression, explaining its varied effects on individuals. Studying this relationship offers deeper insights into human health and potential treatments for skin and immune-related disorders.